2017
DOI: 10.1111/jmi.12569
|View full text |Cite
|
Sign up to set email alerts
|

Using transmission Kikuchi diffraction to characterise α variants in an α+β titanium alloy

Abstract: SummaryTwo phase titanium alloys are important for highperformance engineering components, such as aeroengine discs. The microstructures of these alloys are tailored during thermomechanical processing to precisely control phase fractions, morphology and crystallographic orientations. In bimodal two phase (α + β) Ti-6Al-2Sn-4Zr-2Mo (Ti-6242) alloys there are often three microstructural lengthscales to consider: large (ß10 μm) equiaxed primary α; >200 nm thick plate α with a basketweave morphology; and very fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Orientational analysis between β and α phases ( Figure 5 b,d,f,h) showed that the majority of β-phase demonstrate strict Burgers OR with α-phase crystallites [ 37 , 38 ]. Symmetry axis of Gauss distribution of the spectrum of misorientations is shifted by 1° from ideal BOR, while the deviations do not exceed ±3°.…”
Section: Resultsmentioning
confidence: 99%
“…Orientational analysis between β and α phases ( Figure 5 b,d,f,h) showed that the majority of β-phase demonstrate strict Burgers OR with α-phase crystallites [ 37 , 38 ]. Symmetry axis of Gauss distribution of the spectrum of misorientations is shifted by 1° from ideal BOR, while the deviations do not exceed ±3°.…”
Section: Resultsmentioning
confidence: 99%
“…The phase map and the orientation map are also shown in Figures 13b-c. The orientation relation between secondary alpha plates α s1 , α s2 and β 1 is shown in Figure 13d The procedure for identifying these plane normals and directions is discussed in [29]. It is found that the expected (101) β ||(0001) α and [111] β ||[2110] α Burgers' orientation relation is obeyed [35].…”
Section: Dislocation Activities In Two-phase Regionmentioning
confidence: 99%
“…The stage was tilted to 30 • to make the sample in the TKD holder normal to the electron beam. Detailed description of the orientation relations found by TKD can be found in Tong et al [29].…”
Section: Experimental Descriptionmentioning
confidence: 99%
“…Where such a grain boundary film forms, growth of the Widmanstätten α colony then occurs from the grain boundary α. At higher cooling rates, a basketweave microstructure can be formed [18], where the growing α p plates branch, forming different crystallographic variants [19,20,21]. The formation of a variety of α p and α s variants is likely to be important, because slip bands can be easily transmitted between similarly oriented grains [22], particularly if the α phase is rich enough in Al that low temperature ageing precipitates the α 2 Ti 3 Al phase [23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%